Parasite Fauna and Coinfections in Urban Rats Naturally Infected by the Zoonotic Parasite Angiostrongylus cantonensis - María Teresa Galán-Puchades; Carla Gosálvez; María Trelis; Mercedes Gómez-Samblás; Jennifer Solano-Parada; Antonio Osuna; Sandra Sáez-Durán; Rubén Bueno-Marí; Marius V. Fuentes (Pathogens, 2023)
When the zoonotic parasite of rodents that can cause human neuroangiostrongyliasis, i.e., Angiostrongylus cantonensis, is found in its natural definitive hosts, it is usually reported in isolation, as if the rat lungworm were the only component of its parasite community. In this study, we report the coinfections found in rats naturally infected by A. cantonensis in urban populations of Rattus norvegicus and Rattus rattus in Valencia, Spain. In addition to the rat lungworms, which were found in 14 of the 125 rats studied (a prevalence of 11.20%), 18 other parasite species (intestinal and tissular protists, microsporidia and helminths) were found, some of them with high burdens. Fourteen of these nineteen species found are potential zoonotic parasites, namely Blastocystis , Giardia duodenalis , Cryptosporidium spp., Enterocytozoon bieneusi , Encephalitozoon hellem , Toxoplasma gondii , Brachylaima spp., Hydatigera taeniaeformis s.l. larvae, Hymenolepis nana , Hymenolepis diminuta , Angiostrongylus cantonensis , Calodium hepaticum , Gongylonema neoplasticum and Moniliformis moniliformis . The total predominance of coinfected rats as well as their high parasite loads seem to indicate a trend towards parasite tolerance.